Prekmurje Slovene Grammar. Avgust Pavel’s Vend nyelvtan (1942). - Zoltán, András (Slavia Centralis, 2021)
The author of the article evaluates Pavel's work Prekmurska slovenska slovnica (Vend nyelvtan), which was published in 2013 by the International Publishing House of the Department of Slavic Languages ​​and Literatures at the Faculty of Arts, University of Maribor. The work was edited by Marko Jesenšek and translated from Hungarian by Marija Bajzek Lukač.
Keywords: Prekmurska slovenska slovnica; Vend nyelvtan; Avgust Pavel; grammar; Marko Jesenšek; Marija Bajzek Lukač; translation